Tetrahymena thermophila - Collins, Kathleen, Ph.D (Methods in cell biology ;, 2012)
This new volume of Methods in Cell Biology looks at Tetrahymena thermophila, a model organism in experimental biology. Covering sections on Systems perspectives and Operating principles, chapters are written by experts in the field. With cutting edge material, this comprehensive collection is intended to guide researchers of Tetrahymena thermophila for years to come. Covers sections on systems perspectives and operating principles Chapters are written by experts in the field Cutting-edge material, making this a truly comprehensive collection.